Variability in the Net Ecosystem Productivity (NEP) of Seaweed Farms - Sato, Yoichi; Nishihara, Gregory N.; Tanaka, Atsuko; Belleza, Dominic F. C.; Kawate, Azusa; Inoue, Yukio; Hinode, Kenjiro; Matsuda, Yuhei; Tanimae, Shinichiro; Tozaki, Kandai; Terada, Ryuta; Endo, Hikaru (Frontiers in Marine Science, 2022)
The important role of vegetated ecosystems in the sequestration of carbon has gained strong interest across a wide variety of disciplines. With evidence growing of the potential for macroalgae ecosystems to capture carbon, there is burgeoning interest in applying newfound knowledge of carbon capture rates to better understand the potential for carbon sequestration. Seaweed farms are expected to play a significant role in carbon capture; advocates for the expansion of seaweed farms are increasing in many countries. In general, seaweed farms are expected to be highly productive, although whether they are autotrophic or heterotrophic ecosystems and hence potential exporters of carbon, is under debate. Therefore, we present our investigation of three seaweed farms, two in northern Japan and one in southern Japan. We examine the frequency of autotrophic days and compare potential rates of carbon capture of the seaweed farms with two natural macroalgae ecosystems and one degraded site. We estimated potential carbon capture rates by calculating the net ecosystem productivity from continuous recordings of dissolved oxygen concentrations under natural environmental conditions. The net ecosystem production rates for the natural ecosystems in Arikawa Bay and Omura Bay were equivalent to 0.043 and 0.054 [g C m-2 d-1] m-1, respectively. Whereas, for the degraded ecosystem in Tainoura Bay, it was -0.01 [g C m-2 d-1] m-1. We reveal that the Undaria pinnatifida farm in Matsushima Bay experience autotrophy more often than natural ecosystems, although for seaweed farms producing U. pinnatifida in Hirota Bay and Cladospihon okamuranus at Bise Point, autotrophy was less frequently observed. Nevertheless, up to 14.1 g C m-2 (0.110 g C m-2 d-1) was captured by the production of U. pinnatifida and 3.6 g C m-2 (0.034 g C m-2 d-1) was captured by C. okamuranus, and the total yield of carbon captured during 2021 production season for these farms was 43,385 kg C.